In the Line of Fire: A Provincial Coordinator's Account of Security Challenges in Polio Eradication in Balochistan (2015-2016) - Rehman, Syed Saif Ur; Samad, Muhammad Abdul; Ansari, Muhammad Ibrahim (Annals of Human and Social Sciences, 2026)
The Case Study is a first-person account of my experience as the Provincial Coordinator of the Emergency Operation Center (EOC) of Polio Eradication and Immunizations in the Balochistan province of Pakistan between 2015 and 2016 when there were unprecedented attacks on polio vaccination teams. This paper is a systematic analysis of 30 news articles about security incidents to explore the trends, the perpetrators and the outcomes of the violence on healthcare professionals and security officers. Findings suggest an alarming rise in attacks: starting with the targeted shootings in February 2015 that led to the death of a police officer in Zhob district and then the kidnapping and murder of five members of the team in the same district, and the suicide bombing of an event in January 2016 that killed 15 people outside a polio center in Quetta. Other terror groups including Tehreek-e-Taliban Pakistan (TTP) and Jundullah claimed responsibility citing the 2011 CIA vaccination hoax and alleged sterilization schemes as justification. The ensuing analysis highlights the weaknesses in the intelligence coordination, security measures, and community engagement measures. Despite these challenges, sacrifices by the personals from the Law Enforcement Agencies, the strength of local polio workers and security personnel most of whom continued their duties despite the risks; is a testament to their commitment in protecting children against polio.